Działalność antyalkoholowa Józefa Romana Rybickiego – szkic do biografii - Jackowska, Anna Maria (Polska 1944/45-1989. Studia i Materiały, 2018)
Józef Roman Rybicki zapisał się w historii przede wszystkim jako wybitny działacz niepodległościowy i ważny opozycjonista, mniej jest znany ze swojej aktywnej działalności antyalkoholowej. Zaangażował się w nią najpełniej od 1955 r. Działał najpierw w Komisji Społeczno-Lekarskiej na terenie Pruszkowa, później został członkiem Społecznego Komitetu Przeciwalkoholowego. W tej organizacji przewodniczył m.in. Komisji Wydawniczo-Propagandowej ZG SKP, która prężnie działała pod jego kierownictwem. Sam również publikował teksty antyalkoholowe. W 1972 r. wszedł zarówno w skład Komisji Episkopatu do spraw Trzeźwości, jak i Zespołu Ekspertów Stałej Komisji przy Radzie Ministrów do Walki z Alkoholizmem. Anti-alcohol activities of Józef Roman Rybicki – a sketch to his biography Józef Roman Rybicki has been remembered mainly as an outstanding activist of the Polish opposition underground and important member of the opposition, while his social and civic activities are mentioned much less frequently, despite the fact that his involvement in an anti-alcohol was very significant. Józef Rybicki engaged in anti-alcohol actions already in the 1930s. In later years he was more absorbed by different duties and problems. It was not until the mid-fifties that he was able return to this activity and soon afterwards he started to play an important role on the national scale. He established the Socio-Medical Commission at Pruszków, and at the same time began to work for the Social Anti-Alcohol Committee in Warsaw, where he quickly got promoted, acquiring, among other things, the position of deputy president of the Voivodeship Department of the Social AntiAlcohol Committee in Warsaw. In that capacity he contributed to the establishment of several institutions for detoxification treatment. He was also the head of the publishing and propaganda department of the Social Anti-Alcohol Committee; at the same time he cooperated with an elite periodical Walka z Alkoholizmem (Struggle against Alcoholism). He was the author of several texts (published in fragments or in full) about anti-alcohol actions and campaigns. In 1969 he left the Social Anti-Alcohol Committee but did not stop his anti-alcohol activities, as he was a member of the jury of various competitions in the field of anti-alcohol propaganda. He was also associated with the sobriety movement of the clergy which led to his appointment in 1972 to the Episcopal Commission for Sobriety. In the same year he was made a member of the Experts’ Team of the Permanent Commission at the Council of Ministers for the Struggle against Alcoholism. In that capacity he contributed to the publication in 1981 of the very first great report on problem of alcoholism in Poland.